Metabolization and sequestration of plant specialized metabolites in insect herbivores: Current and emerging approaches - Jeckel, Adriana Moriguchi; Beran, Franziska; Züst, Tobias; Younkin, Gordon; Petschenka, Georg; Pokharel, Prayan; Dreisbach, Domenic; Ganal-Vonarburg, Stephanie Christine; Robert, Christelle Aurélie Maud (Frontiers in Physiology, 2022)
Herbivorous insects encounter diverse plant specialized metabolites (PSMs) in their diet, that have deterrent, anti-nutritional, or toxic properties. Understanding how they cope with PSMs is crucial to understand their biology, population dynamics, and evolution. This review summarizes current and emerging cutting-edge methods that can be used to characterize the metabolic fate of PSMs, from ingestion to excretion or sequestration. It further emphasizes a workflow that enables not only to study PSM metabolism at different scales, but also to tackle and validate the genetic and biochemical mechanisms involved in PSM resistance by herbivores. This review thus aims at facilitating research on PSM-mediated plant-herbivore interactions.